O complexo de soja no norte de Mato Grosso (Brasil):uma perspectiva político-ecológica - Martin Coy; Christoph Huber (Confins)
In addition to introductory conceptual considerations, this article deals with one of the “major” political-ecological research topics: the destruction of the tropical rainforests and savannas. Based on empirical research in the north of Mato Grosso (Brazil) we examine the prevailing destructive human-nature relations. In particular, we focus on the local configuration of the Global Soybean Production Network and its socioecological implications using the example of the “agribusiness-city“ of Sinop and its surroundings.